Quality Assurance in Education: The Development of An Employment Contract-Based Madrassa Principal Supervision Model At Madrassa Aliyah In West Aceh Regency - Herman Herman; Adi Kasman; Sindi Aulia (AL-ISHLAH: Jurnal Pendidikan, 2023)
The development of an employment contract-based madrassa principal supervision model is designed with a contract of employment approach for the principal and teachers (the parties) so that the parties share the responsibility and commitment in implementing the academic supervision program at the madrassa. This study aims to develop a model for the supervision of the principal based on a contract of employment. The research uses the Research and Development method by following the steps, including the preliminary study stage, the model development stage, the model validation stage, and the model improvement stage. In the preliminary study stage, the 1st focus group discussion (FGD) and field studies were carried out, in order to obtain factual data on the implementation of academic supervision so far, and continued with literature studies in order to obtain the results of previous research deemed relevant. At the model design development stage, the and FGD activity was carried out to socialize the conceptual model design and ask for suggestions and input from the madrassa principal and supervisor to improve the developed model. At the model validation stage, the and FGD activity was carried out with experts to test the feasibility of the model on a limited basis through the Delphi technique, to find out how far the effectiveness of the model can be carried out by the madrassa principal. At the last stage, undertaking improvements or revisions to the model according to suggestions and input from the head of the madrassa, supervisors and experts to finalize the model. Then, testing the validity of the data through triangulation of sources. The results of this study indicate that: 1) the current implementation of academic supervision has not received serious attention from the madrassa principal, both in terms of planning academic supervision programs and in implementing academic supervision programs as well as evaluating and following up on the results of observation of class visits supervision, 2) development The employment contract-based madrassa principal supervision model can be an alternative academic supervision model with a contract agreement approach for the principal and teachers (the parties) so that they both have the responsibility and commitment in implementing the academic supervision program at the madrassa. Researchers suggest other researchers to conduct trials with a wider scale in order to find out more accurately and validly about the level of effectiveness of this model.